MANAJEMEN PENDIDIK DAN TENAGA KEPENDIDIKAN DALAM MENINGKATKAN PROFESIONALITAS GURUDI SEKOLAH DASAR - Mutiara Lesmanawati Pergiwa; I Made Sudite Jaya; Hikmatul Aini; Apri Wahyudi (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the management of educators and education personnel (PTK) in improving teacher professionalism in elementary schools through the functions of planning, organizing, implementing, and supervising. This study uses a qualitative approach with a case study design. Research participants consisted of principals, teachers, and education personnel selected using a purposive sampling technique. The results of the study indicate that PTK management has been implemented systematically through the application of POAC (planning, organizing, actuating, controlling) functions. Program planning is carried out based on teacher needs through supervision and discussion, organization is carried out routinely through workshops, training, Teacher Working Groups (KKG), and academic supervision, while supervision is carried out through class supervision, evaluation, and follow-up coaching. The main supporting factors include teacher enthusiasm and a structured program, while inhibiting factors are limited time and facilities. The novelty of this study lies in an in-depth study of the implementation of PTK management in improving teacher professionalism in elementary schools using a qualitative study approach that emphasizes the integration of management functions with continuous academic supervision.